SOCIAL PSYCHOLOGY IN HUMANIZED EDUCATION - de Assunção, Dulcylene Barros; Mendes, Rose Cléia Maria Barros (Seven Editora, 2025)
A model and observation are not enough for the behavior to be practiced; The model should be relevant and of interest to the person who is modeling. This occurs due to the ability to perceive our behaviors in others, for this it is necessary to verify: attention, memory, reproduction and motivation; according to Bandura’s modeling for learning. It is a fact that the corporate can influence us more or less according to the basic foundation made by the first nucleus: family; before the arrival of the coexistence of school, church, club and so on with the other groups that we can be part of throughout life. However, depending on how the base was built, all the others may enhance the abilities more than weaken them with some harmful or permissive behavior. DOI: https://doi.org/10.56238/sevened2025.018-042